Consumption of sugar-sweetened beverages and its association with overweight among young children from China. Issue 13 (6th May 2016) - Yu, Pan; Chen, Yun; Zhao, Ai; Bai, Ying; Zheng, Yingdong; Zhao, Wenzhi; Zhang, Yumei
Abstract: Objective: To fully understand the sugar-sweetened beverage (SSB) consumption status among Chinese young children and to explore its association with weight gain. Design: In this cross-sectional study, data on sociodemographic characteristics, SSB intake and weight/height were collected by means of face-to-face interviews. The intake of SSB among young Chinese children in relation to their age, different characteristics and types of SSB consumed is described, and the association between SSB intake and BMI-for-age Z -score and overweight is explored. Setting: Seven large cities and two villages in China. Subjects: Nine hundred and forty-six healthy children, aged 3–7 years. Results: The proportion of SSB intake among Chinese young children was 80·5 %; 3·4 % were daily consumers, 34·0 % (31·4 %) consumed at least once per week (month). The per capita and per consumer SSB intake was 63·1 9 (sd 100·8) and 78·4 (sd 106·9) ml/d. Children from rural areas consumed twice, or even triple, the amount of SSB as those from urban areas ( P <0·001) and great disparities existed between the types of SSB consumed by urban and rural children. An association was found between increased SSB intake and higher BMI-for-age Z -score ( P <0·05) after adjusting for potential confounders; there was also an association between SSB intake and increased risk of being overweight or obese. Conclusions: The consumption status of SSB in Chinese young children is of concern. There was a positive association between SSB intake and weight gain. Measures should be taken to improve the present situation of SSB consumption among Chinese young children.